Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Produktivitas Kerja Karyawan CV. Lancar Jaya Food. - Septiana, Nur Aida; Gumilar, Dedi (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
This study aims to investigate the influence of organizational culture and work environment on employee productivity at CV. Lancar Jaya Food. The company currently faces challenges in maintaining consistent performance amidst increasing market competition and evolving consumer demands. Initial observations revealed employee dissatisfaction with elements of organizational culture notably in communication practices and reward mechanisms as well as aspects of the physical and psychological work environment. This research adopts a quantitative approach, involving 53 employees selected through purposive sampling. Data were collected using a structured questionnaire, and analyzed through multiple linear regression techniques (without specifying unlicensed software). The findings indicate that organizational culture and work environment both exert a positive and significant impact on employee productivity, both individually and collectively. The t-test results demonstrate a significant effect of organizational culture (t = 3.752, p < 0.05) and work environment (t = 3.210, p < 0.05). Meanwhile, the F-test confirms a joint influence (F = 32.445, p < 0.05), with an R² value of 0.623 meaning that 62.3% of the variance in productivity is attributable to these two factors. This research underscores the critical role of strengthening internal cultural values and cultivating a conducive work environment to enhance motivation and organizational effectiveness. The results offer practical recommendations for human resource management and enrich scholarly discussions on organizational behavior.